Contracting Public Services in New York State: Labour Effects - Hebdon, Robert (Relations industrielles / Industrial Relations, 2006)
This study examines 54 cases of restructuring public services in towns and counties in upstate New York. The 54 cases include 39 cases of privatization in the form of contracting out, nine cases of contracting back in, and six cases of contracting out services to another government. Local government privatization was found to have some harmful effects on workers. Few local employers had adjustment policies to protect affected employees and disproportionate negative impacts were found on women and minorities. Privatization was also found to have significant de-unionizing effects. On the other hand, it had no clear impact on wages and benefits. The role of unions in the restructuring process is more complex than was previously thought. Unions were the catalyst for opposition actions but only in cases involving for-profit restructuring. In the nine cases that involved contracting work back into the public sector, unions supported restructuring changes, and in the six cases of contracting out to another government, union opposition was not significant.